The sacramentality of the Word. A parable of the relationship - García Fernández, Marta (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The objective of the article is to explore the theological possibilities the concept of «sacramentality» present in the Exhortation Verbum Domini (VD 56) offers and its adequacy to decide the complex convergence of «divine-human» of the Scripture. For that the article dedicates two parts. Firstly, goes through the concepts of inspiration and canon and locates the genesis of the concept «sacramentality» and its relation with DV 2. Secondly, elaborates on how this conception based on «deeds and words having an inner unity» (DV 2) completes and enriches the reflection on the nature of the Scripture.